Analysis of Product Quality and Brand Image in Driving Repurchase Intention for Luta Dehumidifier Products at PT. Dwi Mitra Teknindo - Ade Maulana; Oviyan Patra; Evan Nugraha; Hendy Suryana; Adi Ganda Putra (International Journal Labs, 2025)
This study aims to analyze the influence of product quality and brand image on repurchase intention of LUTA dehumidifier products distributed by PT. Dwi Mitra Teknindo. The research background is based on the increasing demand for dehumidifiers in Indonesia after the Covid-19 pandemic, along with the challenges faced by the LUTA brand in building a positive image amid consumer perceptions of Chinese-made products. This study employed a quantitative approach with a descriptive-causal research design. Data were collected through surveys of LUTA consumers in several major cities in Indonesia and analyzed using Structural Equation Modeling (SEM) to examine both direct and indirect relationships among the variables. The findings indicate that product quality has a positive and significant effect on repurchase intention, both directly and through brand image as a mediating variable. Brand image also plays a crucial role in strengthening consumer loyalty towards LUTA products. These results highlight the importance of improving product quality and enhancing brand image as strategic efforts to retain existing customers and support sustainable business growth.